Intravesical and Unilateral Ureterocele with Ipsilateral Kidney Agenesia - A.A Ketabchi (Journal of Kerman University of Medical Sciences, 2003)
This is a report of a rare case of intravesical and unilateral ureterocele in a young man (25 years old) with ipsilateral kidney agenesia. He was referred to our urology clinic with frequent retention. Ultimate diagnosis made by US, IVP and CT Scan. This ureterocele operated via cystostomy.